Impelementasi Pelatihan Desain Grafis dalam Mendukung Pembelajaran dan Literasi Digital pada Siswa MTs. Al-Hadi II - Ikhsan, M. Fajratul; Ikra Muhibban Ananta; Agung Fatwanto (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This community service program is motivated by the issue of low levels of students’ productive digital literacy, particularly in their ability to create educational visual content that supports learning. The program focuses on developing students’ digital literacy through graphic design training integrated into academic projects at Madrasah Tsanawiyah Al-Hadi II. The objective of this community service activity is to enhance students’ ability to utilize digital technology in a creative, communicative, and responsible manner, enabling them not only to act as consumers of digital content but also as creators of educational visual works. The method employed is a participatory and collaborative approach using a project-based learning strategy combined with hands-on training. The activities were conducted through several stages, including preparation, delivery of digital literacy and basic graphic design principles, guided practice in creating learning posters, a design competition, and documentation and evaluation. The results indicate an improvement in students’ productive digital literacy, as reflected in increased confidence in expressing ideas visually, improved ability to use digital devices and graphic design applications for academic purposes, and the production of communicative and creative learning posters. In addition, the program contributed to the development of a technology-based creative learning culture within the school environment and strengthened collaboration between higher education institutions and secondary schools as community service partners.